Impact of telemedicine on the clinical outcomes and healthcare costs of patients with chronic heart failure and mid-range or preserved ejection fraction managed in a multidisciplinary chronic heart failure programme: A sub-analysis of the iCOR randomized trial. (January 2020) - Jiménez-Marrero, Santiago; Yun, Sergi; Cainzos-Achirica, Miguel; Enjuanes, Cristina; Garay, Alberto; Farre, Nuria; Verdú, Jose M; Linas, Anna; Ruiz, Pilar; Hidalgo, Encarnación; Calero, Esther; Comín-Colet, Josep
Background: The efficacy of telemedicine in the management of patients with chronic heart failure and left ventricular ejection fraction ≥40% is poorly understood. The aim of our analysis was to evaluate the efficacy of a telemedicine-based intervention specifically in these patients, as compared to standard of care alone. Methods: The Insuficiència Cardiaca Optimització Remota (iCOR) study was a single centre, randomised, controlled trial, designed to evaluate a telemedicine intervention added to an existing hospital/primary care multidisciplinary, integrated programme for chronic heart failure patients. 178 participants were randomised to telemedicine or usual care, and were followed for six months. For the present sub-analysis, only iCOR participants (n = 116) with left ventricular ejection fraction ≥40% were included. The primary study endpoint was the incidence of an acute non-fatal heart failure event, defined as a new episode of worsening of symptoms and signs consistent with acute heart failure requiring intravenous diuretic therapy. The healthcare-related costs in each study group were also evaluated. Results: The incidence of the first occurrence of the primary endpoint was significantly lower in the telemedicine arm (22% vs 56%, p <0.001), with a hazard ratio of 0.33 comparing to the usual care arm (95% confidence interval 0.17–0.64). Telemedicine was also associated with lower mean overall chronic heart failure care-related costs compared to usual care (8163€ vs 4993€, p =0.001). The results were consistent in both left ventricular ejection fraction of 40–49% and left ventricular ejection fraction ≥50% patients. Conclusions: Our results suggest that telemedicine is a promising strategy for the management of chronic heart failure patients with left ventricular ejection fraction ≥40%. These findings should be replicated in larger cohorts.